First-autumn dispersal of hand-reared Mallard - Boyd, Hugh; Harrison, Jeffery (Wildfowl, 1962)
Recoveries of young Mallard in their first season are used to compare the dispersal of hand-reared and of wild ducks in Britain. The only important difference is in the proportion of birds moving away from the point of release: hand-reared birds are less likely to travel far than wild ones. This favours the building-up of local populations by the use of hand-reared birds.